The twin deficit hypothesis in the MENA region: Do geopolitics matter? - Sarah El-Khishin; Jailan El-Saeed (Economies, 2021)
This paper examines the relationship between fiscal and external balances in MENA oil versus non-oil countries in the context of the twin deficits hypothesis (TDH) using Panel Vector Autoregression- Generalized Methods of Moments PVAR GMM estimation, Granger Causality and IRFs. The essence of this analysis is to assess the vulnerability of fiscal and external balances to oil price dynamics and regional geopolitics in the region. Results show that a twin-deficit problem exists in MENA oil-rich countries only while the problem does not exist in non-oil ones. This affirms the hypothesis that oil dependence results in high fiscal vulnerability to geopolitical shocks that automatically transmits to external balances. While a TDH isn't proven to exist in non-oil countries, fiscal and external balances problems result from longstanding structural factors. A high reliance on tourism revenues and remittances as main sources of foreign currency receipts (together with poor tax administration and enlarged current spending bills) makes those countries more vulnerable to domestic and external shocks; reflected in both growing fiscal and current account deficits. A large imports sector and relatively poor exporting capacity also contribute to weakening external accounts. The main policy recommendations for MENA oil-rich countries rely in the importance of strengthening the non-oil sector in order to diversify domestic sources of revenues. Adopting flexible exchange rates is recommended to decrease the vulnerability of the external shocks to oil price dynamics. For non-oil MENA regions, fiscal consolidation, reforming current spending and strengthening tax administrations are crucial to improve fiscal performance. Export-led growth strategies and inclusive growth policies would also contribute to improving external accounts in the examined economies.
Keywords: 330; budget balance; current account balance; MENA region; non-oil countries; oil countries; PVAR modeling; twin deficit hypothesis